A new tribe and species of Clastopterinae (Hemiptera: Cercopoidea: Clastopteridae) from Africa, Asia and North America - Hamilton, K.g. Andrew (Zootaxa, 2015)
Additional evidence supports the inclusion by Hamilton (2001) of Machaerotinae in Clastopteridae. The former Clastopteridae (Clastopterinae sensu Hamilton, 2001) is revised to include Sepulliini (tr. nov.) Clastopterini includes a fossil genus Prisciba Poinar & Brown and the extant Clastoptera with 2 new species both from North America, and Iba Schmidt from the old-world. The last of these has 3 species (1 new), 2 from the Philippines and 1 in subgenus Parahindoloides Lallemand, stat. nov., from Borneo. Sepulliini includes 5 genera and 52 species from Africa, India and southeast Asia that were formerly included in “Aphrophoridae” but are now transferred to the redefined subfamily Clastopterinae, linking Clastopterini to Zygonini of the subfamily Machaerotinae. Sepulliini includes 24 newly described species: 2 species of Beesoniella Lallemand from India, and 1 of Grellaphia Schmidt from the Philippine Islands; and from continental Africa 2 species of Sepullia Stål from Ethiopia and Angola, Taphrotylus insignificans gen. & sp. nov. from Madagascar and 18 new species of Tremapterus Spinola, making Tremapterus (including Abbalomba Distant, Nyanja Distant and Patriziana Lallemand as subgenera) the largest and most widespread genus in Sepulliini. Its 38 species in sub-Saharan Africa include 2 new subgenera: Selenion (1 species) and Tremiziana (4 species). In this study, 25 new combinations are created: 20 in Tremapterus with T. major Jacobi (1910), described from Mt. Kilimandjaro, and T. occidentalis Schumacher (1912), described from above 1800 m on Mt. Cameroon transferred to Witteella Lallemand (Cercopidae, Aphrophorinae); Penthimia maculipennis Spinola and Philaenus maculosa Walker are transferred to Clastoptera Germar, and Parahindoloides lumuana Lallemand to Iba. The many new species and new combinations in the old-world fauna of Clastopterinae are included in keys and a checklist.